Deamination reaction mechanisms of protonated amines under hydrothermal conditions. (1st January 2019) - Robinson, Kirtland J.; Gould, Ian R.; Fecteau, Kristopher M.; Hartnett, Hilairy E.; Williams, Lynda B.; Shock, Everett L.
Abstract: Many experimental studies report rates of decomposition for amino acids under hydrothermal conditions without describing the kinetics of competing reactions or definitively characterizing individual reaction mechanisms. As a step toward comprehensive models for amino acid reactivity, this study provides a detailed description of the organic reaction kinetics and mechanisms for deamination of amine functional groups at acidic hydrothermal conditions, which favors their protonated aminium forms. Time series experiments yield hydrothermal deamination rates for model aminum compounds benzylaminium (BAH + ) and α-methylbenzylaminium (α-CH3 -BAH + ), buffered at pH 3.3 at 250 °C and 40 bar (Psat ). Both compounds are primary amines, but the amine group in the former is bonded to a primary carbon while in the latter to a secondary carbon; this difference has implications for reactivity that are relevant for naturally occurring amines. Deamination of the aminiums under these conditions forms alcohols as the major primary products. The deamination mechanisms were investigated by determining the reaction kinetics of ring-substituted BAH + and α-CH3 -BAH + derivatives, which provided information on the nature of charge buildup in the transition state. The results for the deamination of BAH + to form benzyl alcohol support nearly equal contribution from two reaction mechanisms, specifically unimolecular nucleophilic substitution (SN 1, kSN1 ≈ 2.4 × 10 −6 s −1 ) and bimolecular nucleophilic substitution (SN 2, kSN2 ≈ 2.7 × 10 −6 s −1 ), while α-CH3 -BAH + deaminates almost exclusively via a much faster SN 1 mechanism ( kα ≈ 7.6 × 10 −4 s −1 ). These observed rates reinforce the notion that previously reported amino acid deamination rates may have resulted from catalysis mechanisms associated with certain reaction vessel materials ( e.g., Pyrex and stainless steel). The observation of two competing mechanisms for BAH + deamination/hydration implies that extrapolation of deamination rates to other temperatures is currently unreliable, since this is likely to be accompanied by a change in the predominant mechanism. However, this work establishes that mechanistic contributions can be quantified, which will enhance the accuracy of extrapolating deamination rates across the temperature and pH ranges common to aqueous geochemical environments.